Zakat for Economic Empowerment of The Poor in Indonesia: Models and Implications - Hafas Furqani; Ratna Mulyany; Fahmi Yunus (IQTISHADIA, 2018)
Sustainable wellbeing is one of the goals of zakat distribution whereby  the poor (mustahiq) are not only able to survive by having the basic needs fulfilled, but also are able to work and fulfill his needs and his family independently. The mustahiq independency is important to solve the problem of inequalities in society, marginalization, unemployemnt and poverty. This can only be achieved if zakat is able to used as a means for economic empowerment of the poor that would increase their capacity and enable them to become enterpreneur and hence able to fulfil their needs by themselves.  This article attempts to observe various zakat productive programs initiated by zakat institutions in Indonesia and also analyze their implications in empowering the poors and increase their level of wellbeing. The case study in this paper is Baitul Mal Aceh and Baznas Indonesia.